Disease characteristics and outcomes in younger adults with primary and secondary myelofibrosis. (13th June 2016) - Beauverd, Yan; Alimam, Samah; McLornan, Donal P.; Radia, Deepti H.; Harrison, Claire N.
Abstract: Myelofibrosis (MF) is a rare haematopoietic disorder, commonly diagnosed in the 6th decade: less than 20% are diagnosed before the age of 50 years. In this retrospective study we included all patients given a diagnosis of World Health Organization‐defined primary or secondary MF when aged ≤50 years. Forty‐three patients with a median age of 43 years were included. Median follow up was 44 months. Twenty‐two (51%) harboured the JAK2 V617F mutation, 18/43 (42%) CALR, 0/43 (0%) MPL mutations and 3/43 (7%) were 'Triple Negative' (TN). At the time of diagnosis, no significant differences existed in haematological and clinical phenotypes between JAK2, CALR and TN patients. The frequency of splenomegaly was greater ( P  =   0·047) in the JAK 2‐mutated group compared to CALR ‐mutated patients. In the whole cohort, the 5‐year probability of developing anaemia, thrombocytopenia and marked leucocytosis was 24%, 10% and 13% respectively. Finally, the cumulative incidence of thrombotic events and progression to acute myeloid leukaemia was 1% and 0·5% patient‐year respectively. No death was reported during the follow‐up. These findings suggest that MF in younger patients may have a more indolent course when compared to older patients.